Baker exegetical commentary on the New Testament : 1 Peter - Jobes, Karen H. (Grand Rapids, MI. Baker Academic, 2022)
In this new edition in the award-winning BECNT series, leading evangelical biblical scholar Karen Jobes offers a substantive commentary on 1 Peter. The first edition, widely regarded as one of the leading commentaries on 1 Peter, has sold over 22,000 copies. The second edition takes recent scholarship into account and has been updated and revised throughout. Jobes takes a historical-grammatical approach to exegeting 1 Peter and considers the possibility that the original readers of the letter were actual exiles who had known Peter in some other location, probably Rome. She analyzes each discourse unit of the Greek text with a view toward not only what the letter meant in its original setting but how it speaks to readers today. As with all BECNT volumes, this commentary features an acclaimed, user-friendly design and admirably achieves the dual aims of the series--academic sophistication with pastoral sensitivity and accessibility--making it a useful tool for pastors, church leaders, students, and teachers.
Introduction to 1 Peter -- A greeting to the Christian diaspora of Asia Minor (1:1-2) -- The opening of the letter : reassurance for God's people (1:3-2:10) -- As God's people, live godly lives (2:11-4:11) -- Consolation for the suffering flock (4:12-5:11) -- The letter closing : final words and greetings (5:12-14) -- Excursus : the syntax of 1 Peter : how good is the Greek?
Includes bibliographical references and index.
English text, partially translated from the Ancient Greek.
Keywords: Bible. -- Commentaries; Commentaries